Сучасні наукові уявлення щодо взаємодії громадянського суспільства і поліцейських структур - Субота, С. І.; Subota, S. I. (Право і безпека. - 2015. - № 3 (58). - С. 103–108., 2015)
Проаналізовано сучасні наукові уявлення щодо взаємодії громадянського суспільства і поліцейських структур. Установлено, що в пошуках оптимальної моделі функціонування нової української поліції та взаємодії її з громадянським суспільством учені-правознавці підтримують єдину точку зору: модель «служіння суспільству» є найпридатнішою для сучасного етапу розвитку правової держави і громадянського суспільства.

The current scientific ideas about the interaction between civil society and police structures are analyzed. It is found out that modern scholars in the field of law consider civil society and the state traditionally interrelated and interdependent legal phenomena. It is proved that the state is created by civil society (people) and derives from it. It is the guarantor of the implementation of needs of civil society and must serve its interests and needs. The new Ukrainian police as a state agency, which is a part of the mechanism of the state, has to act on its behalf and in the interest of the public. Special attention is paid to the fact that in the search for the optimal model of the new Ukrainian police functioning and its interaction with civil society scholars in the field of law maintain a single point of view: the model of «service to the public» is the most suitable for the modern stage of development of the rule of law state and civil society. It is emphasized that the scholars, who do not keep talking about electing the model of police «service to the public», determine the need of its socialization, orientation of police structures on the function of providing public services, close cooperation and interaction between police (militia) and civil society as one of the priorities of the new Ukrainian police and its essential purpose.

Проанализированы современные научные представления о взаимодействии гражданского общества и полицейских структур. Установлено, что в поисках оптимальной модели функционирования новой украинской полиции и взаимодействии её с гражданским обществом учёные-правоведы поддерживают единую точку зрения: модель «служения обществу» является наиболее соответствующей требованиям современного этапа развития правового государства и гражданского общества в Украине.
Subota, S.I. (2015), “Modern scientific ideas concerning the interaction of civil society and police structures” [“Suchasni naukovi uiavlennia shchodo vzaiemodii hromadianskoho suspilstva i politseiskykh struktur”], Pravo i Bezpeka, No. 3, pp. 103–108.
Субота, С. І. Сучасні наукові уявлення щодо взаємодії громадянського суспільства і поліцейських структур // Право і безпека. - 2015. - № 3 (58). - С. 103–108.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; громадянське суспільство; суспільство; правоохоронні органи; поліція; міліція; поліцейські структури; civil society; society; law enforcement agencies; police; militia; police structures; гражданское общество; общество; правоохранительные органы; полиция; милиция; полицейские структуры